The Phenomenon of Collective Violence Among Children: A Criminological Analysis of a Beating Case Resulting in Death in Karawang Regency - elanti fatayatun khoiroh; Indah Sri Utari (Universitas Negeri Semarang, 2026)
This study examines children's involvement in collective violence resulting in death in Karawang Regency, focusing on criminogenic factors and the patterns and characteristics of group violence. The main issues discussed are how social, environmental, and individual factors influence children's involvement in fatal gang violence, and how patterns of collective violence among children are formed. This study aims to analyze the causes of children's involvement in collective violence, identify the patterns and characteristics of these collective actions, and assess the criminogenic factors that influence children's behavior. The method used is normative juridical legal research supported by an empirical approach and a criminological perspective. Data were obtained through a literature review of laws and regulations, court decisions, and scientific literature, as well as field studies in the form of interviews with public prosecutors handling related cases. All data were analyzed qualitatively using a descriptive approach. The results indicate that children's involvement in collective violence is influenced by weak parental supervision, negative peer influence, and the psychological conditions of adolescents who tend to be impulsive and emotionally dominated. Group dynamics reinforce aggressive behavior and reduce individual responsibility. This study concludes that preventing collective violence by children requires integrated efforts through law enforcement, strengthening the role of the family, fostering a positive social environment, and early intervention against criminogenic risk factors.